Mediação ambiental : a tutela extrajudicial como instrumento complementar de acesso à justiça - Figueiredo, Luciana Monduzzi (2013)
The study aims to demonstrate the feasibility of extrajudicial environmental protection as a mechanism for access to justice. It was discussed initially on the peculiarities of the environmental good, which protection should be based on a preventive and precautionary behavior in order to ensure balanced and healthy environment for present and future generations. Emphasized the complexity and speed of events in contemporary society, so that the instruments of access to justice should be, the same way, fast and effective for solving an environmental crisis. To do so, it is necessary a reinterpretation of the concept of access to justice. In a simplistic view, justice would be monopoly of the judicial function, that, overwhelmed, time consuming and technically deficient, can not satisfactorily resolve disputes. Added to this factor, the argument is that the judiciary, to resolve the legal dispute, is often not able to compose the underlying crises, which is of fundamental importance to the environmental good, especially in the ethical and sociological aspect. It has been shown that the distribution of justice can be done through judicial and extrajudicial instruments, which should be chosen according to the peculiarities of the conflict. In the process of extrajudicial negotiation, not always the reparation by the duty to indemnify is proposed (win-lose model), but a harmonization between the conflicting interests (win-win model), always from the perspective of environmental protection (as well greater). The focus, then, is the problem and not the people and the formal issues involved. With this reasoning, environmental mediation proves to be an effective way, since not only aims to resolve the controversy, but to develop a new continuous and lasting relationship of parts to the environment, through the mediation of a third party prepared with multidisciplinary techniques. Despite the absence of specific legislation, mediation, inclusive, is already a reality in practice in Brazil, given the inherent advantages compared to a bureaucratized legalization debate.